Climate change, labelling, international standards and the Technical Barriers to Trade Agreement: Are they in (dis)harmony? - Michelle Ayu Chinta Kristy; Joachim Monkelbaan (Journal of World Trade Studies, 2015)
Climate change and trade are two separate realms that inevitably interact with each other. Trade, representing more than half of global GDP by some accounts, may play a pivotal role in efforts to combat climate change and to reduce greenhouse gas emissions. The WTO Agreements were not specifically composed for climate change purposes. Labelling and international standards may be used as a trade tool whose application may influence consumer preferences and shift markets. In the context of climate change, labelling may effectively inform consumers about international standards and, in particular, the carbon footprint of products. In the context of WTO Agreements, labelling is governed by the Agreement on Technical Barriers to Trade (TBT Agreement). This article investigates the compatibility of the TBT Agreement in governing labelling aimed at mitigating climate change and it elaborates tensions at the nexus between climate change and trade in the context of labelling. This article eventually argues that climate change, labelling, international standards and the TBT Agreement can be in harmony. Further arrangements, which will close more gaps in the relation between the TBT Agreement and measures aimed at combating climate change, are required to alleviate (possible) tensions in practice.